Asālību al Amri wa al Nahwi li ’Aḥādīṡi al Nikāḥi fī Kitābi Bulughi al Marāmi: Dirāsatun Taḥlīliyyatun fī ‘Ilmi al Ma’ānī - Cahyadi, Agustian Harly; Yusuf, Muhammad (Al-Uslub: Journal of Arabic Linguistic and Literature, 2023)
Hadith are words, deeds, decisions that are based on the Prophet Muhammad SAW. If we want to understand a hadith, we must understand various kinds of knowledge, one of which is the science of Balaghah which includes commands and prohibitions. The author finds many words "commands and prohibitions" in the Marriage Chapter as an example of "tazawwaju" which means "marry". Most people when they hear the word they will think it is just a command word. But in fact it has hidden benefits in the hadith. This study aims to find out about the commands and prohibitions, to find out the meaning and benefits contained in the Hadith Chapter of Marriage (Bulughul Marom). This study uses a qualitative research approach or library method, namely the method of collecting data with the method of documentation through books, magazines, journals, and other literature related to this research with the aim of forming a theoretical basis. The data analysis used is descriptive data analysis, namely the analytical technique used to analyze the data by describing the data that has been collected without any intention of making generalizations from the results of the study. The author examines the word commandment in 59 places, and the word prohibition in 17 places in the hadith Bulughul Marom.